Spatial-temporal variations of cultivated land compensation and its compensation mechanism in mainland China - Chen, Shulin; Pei, Ben (Environmental impact assessment review, 2025)
Cultivated land compensation can alleviate the conflict between cultivated land protection and socio-economic development. Exploring the spatial-temporal trends of cultivated land compensation, and formulating a scientific and reasonable compensation mechanism are important to achieve sustainable development. To analyze the spatial-temporal changes of the area, comprehensive non-market value, and compensation amount of cultivated land in mainland China, this paper constructed a comprehensive non-market value evaluation framework including positive ecological, negative ecological, and social values, and designed a feasible cultivated land compensation model. In terms of cultivated land area, the cultivated land area indicated an overall surplus condition, and the total net surplus area during 2000–2021 was 54.4 million hectares per year. On a spatial scale, the net surplus districts were concentrated in the north and the center of China, while the net deficit districts were in the developed areas along the southeast coast. In terms of comprehensive non-market value, except for negative ecological value, all other non-market values had increased. On a spatial scale, the coupling relationship between comprehensive non-market value and regional economic development was obvious, presenting a higher value observed in the southeastern coastal developed provinces, and a lower one in the developing inland provinces. In terms of compensation amount, the total payment amount of the payment districts was difficult to cover the total compensation amount of the compensated districts, a certain compensation gap between the two appeared, averaging 6.03 trillion RMB during 2000–2021. On a spatial scale, the payment districts were mainly distributed in the southeastern coastal area, and the number of the payment districts was smaller than that of the compensated area. It is suggested that we should clarify the subject of cultivated land compensation and identify its rights and responsibilities, highlight the leading role of the central government and give full play to the main role of all levels of government, adopt diversified market financing instruments according to local conditions, and formulate relevant supporting security systems. [Display omitted] •The estimated cultivated land compensation amount is reasonable and feasible.•The payment amount was significantly less than the compensated amount.•The payment capacity improved and the reimbursement requirements dropped.•A feasible compensation mechanism was proposed.